2021
DOI: 10.1016/j.jbc.2021.100819
|View full text |Cite
|
Sign up to set email alerts
|

The dipeptide prolyl-hydroxyproline promotes cellular homeostasis and lamellipodia-driven motility via active β1-integrin in adult tendon cells

Abstract: The dipeptide prolyl-hydroxyproline promotes cellular homeostasis and lamellipodiadriven motility via active β1-integrin in adult tendon cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 93 publications
(154 reference statements)
0
18
0
Order By: Relevance
“…Yazaki et al indicated that collagen-derived oligopeptides, such as Pro-4Hyp and Gly-Pro-4Hyp, were incorporated into the mouse skin after oral administration of collagen hydrolysate 5 . In addition, several studies reported cellular uptake of collagen-derived oligopeptides, such as by skin fibroblasts 40 , osteoblasts 10 , and tenocytes 12 . Tenocytes are suggested to internalize Pro-4Hyp through multiple pathways, including integrin-mediated endocytosis 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Yazaki et al indicated that collagen-derived oligopeptides, such as Pro-4Hyp and Gly-Pro-4Hyp, were incorporated into the mouse skin after oral administration of collagen hydrolysate 5 . In addition, several studies reported cellular uptake of collagen-derived oligopeptides, such as by skin fibroblasts 40 , osteoblasts 10 , and tenocytes 12 . Tenocytes are suggested to internalize Pro-4Hyp through multiple pathways, including integrin-mediated endocytosis 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Runx2 and Smad form a transcriptional complex. In a recent study (2021) 20 , it was shown that Pro-Hyp promotes differentiation of tendon cells with modulation of lineage-specific factors and induces chemotactic activity, proliferation, and type I collagen-network organization. In our recent study using primary fibroblasts derived from mouse skin tissue 32 , Pro-Hyp selectively stimulates migration and proliferation of fibroblasts, which express p75 neurotrophin receptor (p75 NTR ) when cultured on collagen gels.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that collagen-derived peptides have biological activities 16 , and ingested hydrolysates accelerate wound healing reactions in patients with pressure ulcers 17 and also enhance anti-aging improvements on the facial skin, including moisture, elasticity, wrinkles, and roughness 18 . Moreover, it has been shown that Pro-Hyp promotes cellular differentiation in osteoblastic cells 19 and tendon cells 20 by modulating intracellular signal pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Runx2 and Smad form a transcriptional complex. In a recent study (2021) 20 , it was shown that Pro-Hyp promotes differentiation of tendon cells with modulation of lineage-speci c factors and induces chemotactic activity, proliferation, and type collagennetwork organization. In our recent study using primary broblasts derived from mouse skin tissue 33 , Pro-Hyp selectively stimulates migration and proliferation of broblasts, which express p75 neurotrophin receptor (p75 NTR ) when cultured on collagen gels.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that collagenderived peptides have biological activities 16 , and ingested hydrolysates accelerate wound healing reactions in patients with pressure ulcers 17 and also enhance anti-aging improvements on the facial skin, including moisture, elasticity, wrinkles, and roughness 18 . Moreover, it has been shown that Pro-Hyp promotes cellular differentiation in osteoblastic cells 19 and tendon cells 20 by modulating intracellular signal pathways.…”
Section: Introductionmentioning
confidence: 99%